CHARACTERIZATION AND COMPARISON OF HUMORAL IMMUNE RESPONSES IN BALB/c MICE IMMUNIZED WITH CRUDE PbS AND PbRTSG ANTIGENS OF Plasmodium berghei ANKA - Cyuzuzo Callixte (2021)
Malaria is an infectious disease caused by apicomplexan from the genus Plasmodium which has uniqueness to infect and develop inside the erythrocytes. It is transmitted by the bite of Anopheles mosquitoes infected with malaria parasite. This research was intended to characterize and compare humoral immune responses in BALB/c mice immunized with crude P. berghei ANKA schizont rich (PbS-Ag) and P. berghei ANKA ring trophozoite schizont gametocyte (PbRTSG-Ag) antigens. The two antigens were prepared and emulsified into Complete and Incomplete Freund’s adjuvants before immunization. ELISA was employed to titrate the IgG antibody and the proteins of the antigens were characterized by SDS-PAGE and Western blot. ELISA results showed that IgG levels in the three groups were significantly different (p= 0.000) and the humoral immune response to PbS-Ag was significantly high with IgG levels ranging from 0.950pg/mL to 1.294pg/mL compared to IgG levels against PbRTSG-Ag that ranged between 0.868pg/mL and 1.074pg/mL(p=0.049). The IgG titers in the negative control group varied from 0.737pg/mL to 0.810pg/mL and was significantly different from the humoral response in the PbRTSG-Ag group (p=0.001) and the PbS-Ag group (p=0.001). The anti PbS-Ag antibody recognized the specific protein of PbS-Ag with a molecular weight of 66.43 kDa and the anti PbRTSG-Ag antibody recognized the specific protein with a molecular weight of 58.45 kDa. In addition, anti-PbS-Ag antibody also recognized the same protein with a molecular weight of 58.45 kDa. Thus, this protein with 58.45 kDa is a common epitope presents on both antigens that was recognized by both antibodies.